The “mid”-Cretaceous (Lower Cenomanian) Continental Vertebrates of Gara Samani, Algeria. Sedimentological Framework and Palaeodiversity - Benyoucef, Madani; Pérez-García, Adán; Bendella, Mohamed; Ortega, Francisco; Vullo, Romain; Bouchemla, Imad; Ferré, Bruno (Frontiers in Earth Science, 2022)
Excellent outcrops of the upper part of the “Continental Intercalaire” deposits occur in the Gara Samani area, southern Algeria. These strata are recognised herein as belonging to the Gara Samani Formation, which is composed of the Samani Vertebrate-rich Sand Member, the Samani Sandstone Member and the Méguidène Stratified Sand Member. The first two members are from a fluvial system and the last member corresponds to an aeolian (dune and interdune) system. They have preserved one of the most diverse continental vertebrate faunas of latest Albian–early Cenomanian age yet known from northern Africa. Most of the taxa identified there, cited for the first time for the ‘mid’-Cretaceous of Algeria, have not been analysed in detail so far; and manyof themhave never been figured. The faunal list of vertebrates from this locality was supplemented thanks to detailed analysis of new and relatively abundant finds. As a consequence, the Gara Samani vertebrate assemblage is recognised as composed of elasmobranchs (two Hybodontiformes, i.e., Tribodus sp. and Distobatidae indet.; and a Batoidea, Onchopristis numida), actinopterygians (Bawitius sp., Adrianaichthys sp., Obaichthys africanus, and Calamopleurus africanus), sarcopterygians (Mawsoniidae indet. and the Dipnoi, cf. Lavocatodus humei and Neoceratodus africanus), testudines (at least two Pelomedusoides, one of them being a representative of Araripemydidae), crocodyliforms (all remains being compatible with Neosuchia, represented at least by Elosuchus broinae), ornithocheirid pterosaurs, and non-avian dinosaurs (titanosauriform sauropods and at least two theropods, Spinosaurus aegyptiacus and Carcharodontosaurus saharicus). This fauna association displays close similarities to contemporaneous ones from North Africa, especially with that from the Kem Kem beds.